Supply chain agility assessment of an Indonesian humanitarian organization - Rizal Afif Rasyidi; Ratih Dyah Kusumastuti (Journal of Humanitarian Logistics and Supply Chain Management, 2020)
Purpose – The article presents an evaluation of the supply chain agility of the Indonesian humanitarian organization Aksi Cepat Tanggap (ACT). It discusses the flexibility, responsiveness and effectiveness of ACT's supply chain. Design/methodology/approach – The supply chain agility metrics were assessed based on interviews with representatives from ACT and the National Agency for Disaster Management (Badan Nasional Penanggulangan Bencana [BNPB]). Recommendations were made based on the assessment results. Findings – The findings of this study indicated that ACT's supply chain agility maturity was at level 2 or repeatable. This meant that ACT's humanitarian supply chain (HSC) had demonstrated agility only on limited occasions. ACT's supply chain agility can be improved by enhancing the flexibility component. Practical implications – The study shows how to assess the supply chain agility of a humanitarian organization and identify the components/capabilities of agility that need improvement. The same assessment can be conducted by other humanitarian organizations to enhance their supply chain agility to improve their emergency response in the event of a disaster. Originality/value – The study provides insights into the supply chain agility of a locally based humanitarian organization in an emerging country, which is rarely discussed in the literature.